Inter-neuronal signaling mediated by small extracellular vesicles: wireless communication? - Nieves Torres, Damaris; Lee, Sang H (Frontiers in Molecular Neuroscience, 2023)
Conventional inter-neuronal communication conceptualizes the wired method of chemical synapses that physically connect pre-and post-synaptic neurons. In contrast, recent studies indicate that neurons also utilize synapse-independent, hence “wireless” broadcasting-type communications via small extracellular vesicles (EVs). Small EVs including exosomes are secreted vesicles released by cells and contain a variety of signaling molecules including mRNAs, miRNAs, lipids, and proteins. Small EVs are subsequently absorbed by local recipient cells via either membrane fusion or endocytic processes. Therefore, small EVs enable cells to exchange a “packet” of active biomolecules for communication purposes. It is now well established that central neurons also secrete and uptake small EVs, especially exosomes, a type of small EVs that are derived from the intraluminal vesicles of multivesicular bodies. Specific molecules carried by neuronal small EVs are shown to affect a variety of neuronal functions including axon guidance, synapse formation, synapse elimination, neuronal firing, and potentiation. Therefore, this type of volume transmission mediated by small EVs is thought to play important roles not only in activity-dependent changes in neuronal function but also in the maintenance and homeostatic control of local circuitry. In this review, we summarize recent discoveries, catalog neuronal small EV-specific biomolecules, and discuss the potential scope of small EV-mediated inter-neuronal signaling.